2008
DOI: 10.1177/1063426607312536
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Processes in Youth Psychotherapy

Abstract: This study explores hypothesized associations among therapist engagement strategies, therapeutic alliance, client involvement, and treatment outcome in a randomized clinical trial comparing cognitive behavioral psychotherapy and nondirective supportive psychotherapy for adolescents with depressive symptoms who have attempted suicide. Ratings from audiotapes and self-report of the first four sessions for 23 adolescent clients were used. It was expected that therapeutic relationship variables would be equally im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 80 publications
9
46
0
1
Order By: Relevance
“…Early alliance did not predict level of involvement; however, a positive change in the alliance predicted level of involvement. This finding is consistent with previous conceptual work (e.g., Chu et al, 2010; Shirk & Karver, 2006) and a previous study that established a positive relation between the alliance and involvement in CBT for children with depressive symptoms (Karver et al, 2008). Taken together, there is some evidence supporting the assertion that a strong alliance sets the stage for subsequent involvement in CBT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Early alliance did not predict level of involvement; however, a positive change in the alliance predicted level of involvement. This finding is consistent with previous conceptual work (e.g., Chu et al, 2010; Shirk & Karver, 2006) and a previous study that established a positive relation between the alliance and involvement in CBT for children with depressive symptoms (Karver et al, 2008). Taken together, there is some evidence supporting the assertion that a strong alliance sets the stage for subsequent involvement in CBT.…”
Section: Discussionsupporting
confidence: 92%
“…Using observational measures to assess alliance and involvement, Karver et al (2008) found that alliance measured at session three was positively associated with involvement at session four. However, most studies have not focused on in-session client involvement.…”
mentioning
confidence: 99%
“…For example, therapists can be trained to increase certain behaviors associated with strong alliances (e.g., therapist responsiveness; Russell, Shirk, & Jungbluth, 2008) as well as decrease other behaviors associated with weak alliances (e.g., pushing the child to talk; Creed & Kendall, 2005;Karver et al, 2008). Thus, findings suggest that it remains crucial for therapists to continue to focus on the development of the TA while simultaneously attending to specific therapeutic tasks, such as exposure and response prevention.…”
Section: Discussionmentioning
confidence: 90%
“…Past research indicates the value of assessing adolescents' subjective experiences of the therapeutic relationship (Karver et al, 2008). Therefore, we recommend including self-report measures of the alliance in future investigations.…”
Section: A Therapist-i-adolescentmentioning
confidence: 98%